PENGEMBANGAN MODEL UNTUK MEMPREDIKSI KESUKSESAN BISNIS PRODUK BERUPA BARANG - , VANNISA AMALIA L ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Maintaining the existence of products in market, a company should create new products or innovate developed products. Making innovation on products is not sufficient, a company needs innovation on business model as well. Strategies on the innovation of business model have been developed through business model tools. The tools have been using inter-variables relationship assumed going with linier patterns, whereas the relationship quantitatively is able to have non-linear patterns. This study aimed at developing mathematical model which can be used to predict the success of product business with considering the patterns of inter-variable relationship. The mathematical model was used as input in the tools of business model developed in this study. Mathematical model was established through variables gained from 26 strategies canvas of product. The developed model was based on groups of Kanoâs models namely must-be quality, one-dimensional quality, and attractive quality. In this study, the mathematical model consisted of two relationship patterns i.e. linear and exponential patterns. The model was the best chosen one than two other alternative developed models and other models of prior research. The best chosen mathematical model had R2 value 0.983, predicting ability to 1 rank 83%, predicting ability to 2 ranks systematically 67%, predicting ability to 3 ranks systematically 67% and predicting ability to all ranks, overall, 67%. This model was then employed as an input in developing tools of business model. The tools of business model were developed by using spreadsheet software of Microsoft ExcelTM. Variabels of the tools were assessed through the pairwise comparison method and prediction results were assessed through inputs of the chosen mathematical model. The tools was developed to assist users in evaluating the business model of products.